Study guides

Q: Factor 2a2 - 5a 3

Write your answer...

Submit

Related questions

(2a-3)(a-1)

The other factor is 1.

3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)

5a3-45a=-2a2+18 5a(a2-9)=-2(a2-9) 5a=-2 a=-2/5

Factor 5a-15 Factor out the 5; 5(a-3)

Multiply the first and last coefficients.2*3=6What two factors give you six but when combined give you -5-2 and -3Therefore2x-3)(x-1) will be the factored model.

5a4 + 3a3 + 2a2

5a-20=

(2a - 1)(a - 5)

5a

5a(a(a-5)+3)

a(2a + 1)

I'll assume the missing signs are pluses. 7a^2 - 12a + 14

(a - 2)(a^2 + 4)

5a^2 - 5a - 60 ---- 5(a2 + a - 12)

2(a + 7)(a - 6)

2b(5a - 7)(5a + 7)

2a2 - 13a + 15 = (2a - 3) (a - 5)

2(5a - 2)(5a - 2) or 2(5a - 2)2

5a- 2a = 3

a2-5a-14 = (a-7)(a+2) when factored

25a2-30a+9 (5a-3)^2

5a

5a

5a